The Educational Concept of Ki Hajar Dewantara in Kindergarten - Martinah, Martinah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study aimed to track the evolution of the among system implementation in Ki Hajar Dewantara’s Kindergarten students’ educational idea. A qualitative method approach was employed in this study, which was carried out in the villages of Kindergarten (TK) Pembina Kayuagung and Kindergarten (TK) Pertiwi Kayuagung. Interviews, observation, and documentation were used in the research. The Miles and Huberman technique was used to examine the data through the steps of data reduction, data visualization, and researcher data verification. The data analysis results demonstrate that: (1) the Ki Hajar Dewantara educational concept is always applicable; (2) the form of educational activities for Kindergarten children is to develop the senses, such as playing, singing, dancing, and telling stories; (3) the educational process is carried out with a cultural approach, such as traditional games, singing traditional songs, telling stories, and using natural materials as learning media is the uniqueness of the education; and (4) the educational process is carried out with a cultural approach. (4) Internal and external barriers to and enablers of the adoption of the educational idea Ki Hajar Dewantara in the classroom.